A DEEP DIVE INTO IMCI INTEGRATION: ASSESSING PRIMARY HEALTHCARE CENTERS IN PORT HARCOURT - Ahmed , Fatima Ibrahim; Adeoye , Benjamin Oluwaseun (Research Journal of Health, Medicine and Nursing, 2024)
Childhood diseases are a major global health issue, causing millions of deaths each year in low and middleincome countries. To combat this, the World Health Organization introduced the Integrated Management of Childhood Illness (IMCI) strategy in 1992, designed as a standardized tool for nurses and midwives in primary healthcare settings. The IMCI guides healthcare providers through assessment, classification, treatment, counseling, and follow-up for childhood illnesses. This approach helps classify illnesses based on danger indicators and severity, enabling effective treatment. Nigeria adopted the IMCI strategy in 1996, yet consistent training programs have been lacking, resulting in limited improvements in child health. The under5 mortality rate in Nigeria has risen from 128 to 132 deaths per 1,000 live births between 2013 and 2018.